Study on the Transmission Performance of Variable Surface Magnetorheological Driven by Temperature Controlled Shape Memory Alloy - Huang Jin; Wang Xi (Jixie chuandong)
A method of temperature control variable surface magnetorheological transmission is put forward,the magnetorheological fluid is driven by means of a temperature-controlled shape memory alloy spring,so that the working space of the magnetorheological fluid from one to two,the torque that the device can deliver is increased. Based on the characteristics of disk magnetic fluid transmission,the torque transmitted separately before and after the variable face is derived,the influence of temperature on the transmission torque of magnetorheological fluid is explored,and the magnetic field analysis is carried out by ANSYS software. Results show that the magnetic induction intensity in the working space h1 increases with the increase of the radius. In the working space h2,the magnetic induction intensity decreases with the increase of radius and then increases with the increase of radius. In the working space h3,the magnetic induction intensity increases with the increase of the radius. The torque transferred by the device increases by 91. 06% compared with the torque transmitted before the device.